The effectiveness of metabolic resistance training versus traditional cardio on athletic performance: a systematic review and meta-analysis - Tongwu, Yu; Chuanwei, Ding (Frontiers in Physiology, 2025)
IntroductionThe “no pain, no gain” philosophy has long influenced athletic training approaches, particularly in high-intensity workouts like metabolic resistance training (MRT). However, the necessity of discomfort-inducing training for optimal athletic performance remains debatable. This systematic review and meta-analysis examined whether MRT provided comparable or better results than traditional training methods in trained athletes.MethodsA systematic search of PubMed/MEDLINE, Web of Science, Scopus, and SPORTDiscus (January 2004 - December 2024) identified RCTs comparing MRT with traditional training in athletes. Two reviewers screened studies and assessed bias risk using Cochrane RoB 2. Random - effects meta - analyses were conducted for outcomes like VO2max, peak power, sprint performance, blood lactate, time to exhaustion, and jump height. GRADE was used to evaluate evidence certainty.ResultsEleven studies (n = 276 participants) met inclusion criteria. MRT demonstrated a statistically significant improvement in sprint performance (SMD = 1.18, 95% CI: 0.00 to 2.36, p < 0.0001) and countermovement jump height (SMD = 0.80, 95% CI: −0.04 to 1.64, p = 0.0007), indicating notable gains in explosive power. VO2max improvements were observed (SMD = 0.30, 95% CI: −0.19 to 0.79, p = 0.10) but did not reach statistical significance. Peak power output showed a moderate but non-significant positive effect (SMD = 0.54, 95% CI: −2.05 to 3.13, p = 0.55), while blood lactate changes varied widely (SMD = −1.68, 95% CI: −8.58 to 5.22, p = 0.29), reflecting high heterogeneity across studies. Time to exhaustion presented a small positive effect (SMD = 0.23, 95% CI: 0.00 to 0.46, p = 0.18), but without statistical significance. Subgroup analyses revealed that younger adults (19–25 years) and experienced athletes benefited the most from MRT, with low-frequency training (≤2 sessions/week) yielding the most favorable adaptations. Moderator analysis confirmed that sprint performance had the strongest response to MRT, while aerobic measures exhibited more variability.ConclusionThe evidence demonstrates the capacity of MRT to enhance athletic performance comparable to or exceeding traditional training methods while requiring reduced time commitment. These findings suggest that optimal performance adaptations can be achieved through well-designed MRT protocols without necessitating excessive training volumes.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-11-0024, identifier: 36 INPLASY2024110024.